Evaluation of cell death markers and reproductive parameters in models of diabetes mellitus - Dias, Tânia Isabel Rodrigues Amaral (2013)
Diabetes mellitus (DM) represents one of the greatest threats to modern global health and its incidence is rapidly rising worldwide. It describes a metabolic disorder characterized by hyperglycaemia resulting from defective insulin secretion, resistance to insulin action, or both. There are two types of DM, type-1 DM (T1DM) and type-2 DM (T2DM), both associated with male infertility. T1DM is associated with insulin deprivation and although the overall in vivo effects in the reproductive function is well known, there is a lack of studies concerning about the insulin control over the physiological functions of cells from the reproductive system. Importantly, the in vivo studies are often focused after the disease is fully establish, but it is known that a prediabetic state, which is characterized by insulin resistance, precedes the development of DM, especially T2DM. With our work, we aimed to further investigate the association between DM and male infertility by analyzing several apoptotic markers and reproductive parameters. To do so, we simulated type 1 DM in cultured rat Sertoli cells and analyzed the mRNA and protein expression levels of several cellular markers involved in the mitochondrial apoptotic pathway. We also developed an animal model of prediabetes to evaluate the effect of this pathological state in the reproductive parameters as well as in the mitochondrial apoptotic pathway. Our results lead us to suggest that insulin interferes with the interaction between pro and anti-apoptotic proteins. As the interaction of these proteins decide the cell fate and exert a strict control over the apoptotic signaling, insulin has a key role in the maintenance of the spermatogenesis. Our rat model shared many of the clinical and metabolic characteristics of the prediabetic state observed in humans such as glucose resistance and progression from normoglycaemia/normoinsulinemia to moderate hyperglycaemia/hyperinsulinemia due to food intake. This prediabetic state induced important alterations in cauda epididymis spermatozoa morphology showing that these animals may develop subfertility or fertility problems. The apoptotic signalling in cauda epididymis spermatozoa of the high-energy (HED) fed animals presented lower Bax mRNA levels and lower cytC protein levels although the apoptotic endpoint, caspase-3 activity, was not altered. This suggests that the apoptotic process may be controlled by other mechanisms rather than the mitochondrial pro-apoptotic proteins, such as the anti-apoptotic cellular systems. Those two experimental models led us to conclude that the subfertility/infertility problems caused by DM may be mediated by insulin, which has an important effect in the regulation of the interaction between pro and anti-apoptotic proteins and special attention must be taken in the prediabetic state where crucial alterations in rat spermatozoa occurred. Due to the rising incidence and associated complications of DM and male infertility it is crucial to further investigate in these two systems to isolate possible mechanisms and evaluate the overall effects as a strategy to develop possible therapeutics.